Linezolid Pharmacokinetics in Critically Ill Patients: Continuous Versus Intermittent Infusion - Ligia-Ancuța Hui; Constantin Bodolea; Adina Popa; Ana-Maria Vlase; Elisabeta Ioana Hirișcău; Laurian Vlase (MDPI AG, 2024)
Background: Linezolid has been found to have considerable interindividual variability, especially in critically ill patients, which can lead to suboptimal plasma concentration. To overcome this shortcoming, several solutions have been proposed. These include using loading dose, higher maintenance doses, and dose stratification according to the patient's particularities, therapeutic drug monitoring, and drug administration via continuous infusion (CI) instead of intermittent infusion (II). In the present study, we aim to compare the pharmacokinetic (PK) parameters of linezolid after administration as II versus CI to critically ill patients. Methods: In a prospective study conducted in an intensive care unit, we compared the same two daily doses of linezolid administered via II versus CI. The serum concentration was measured, and pharmacokinetic parameters were calculated. The pharmacokinetic/pharmacodynamic (PK/PD) indices for efficacy chosen were area under the concentration-time curve at steady state divided by the minimum inhibitory concentration over 80 (AUC24-48/MIC > 80). Results: Greater serum concentration variability was observed in the II group than in the CI group. The %T > MIC > 80% was achieved for MICs of 1 and 2 µg/mL 100% of the time, whereas for the II group, this was 93% and 73%, respectively. AUC24-48/MIC > 80 was reached in 100% of cases in the CI group compared with 87% in the II group for a MIC of 1 µg/mL. Conclusions: The two infusion methods may be used comparably, but utilizing CI as an alternative to II may have potential benefits, including avoiding periods of suboptimal concentrations, which may enhance safety profiles and clinical outcomes. Considering the relatively few studies performed on linezolid to date, which are increasing in number, the results of the present study may be of interest.